2021
DOI: 10.1002/pi.6292
|View full text |Cite
|
Sign up to set email alerts
|

Vinyl‐functionalized polyborosiloxane for improving mechanical and flame‐retardancy performances of silicone rubber foam composites

Abstract: In this work, we first synthesized vinyl-terminated polyborosiloxane (pBS) filler, and then incorporated it into silicone rubber foam (SRF) matrix to prepare composite materials through a simple chemical dehydrogenative foaming method under ambient conditions. The pBS filler with reactive groups could form physical and chemical crosslinking networks in SRF, leading to an excellent dispersion level of pBS in the SRF matrix. Moreover, the inserted pBS could remarkably improve the mechanical and flame-retardancy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…They are usually chosen as an appropriate tool for blowing agents but are also promising candidates to serve as temperature-responsive microcapsules for self-sensing and deformation. Interestingly, silicone rubber foam (SRF) with a porous structure is formed after SR based on microspheres deforms, which contributes to high temperature resistance and thermal insulation property. , As for ablation resistance strengthening, zinc borate (ZB), a common fluxing agent and flame retardant, is conducive to form the SR ceramic body, effectively preventing further ablation. , This inspired us to study whether the foaming process and ablation strengthening can be coupled to achieve intelligent deformation and improve ablation resistance through synergistic effects.…”
Section: Introductionmentioning
confidence: 99%
“…They are usually chosen as an appropriate tool for blowing agents but are also promising candidates to serve as temperature-responsive microcapsules for self-sensing and deformation. Interestingly, silicone rubber foam (SRF) with a porous structure is formed after SR based on microspheres deforms, which contributes to high temperature resistance and thermal insulation property. , As for ablation resistance strengthening, zinc borate (ZB), a common fluxing agent and flame retardant, is conducive to form the SR ceramic body, effectively preventing further ablation. , This inspired us to study whether the foaming process and ablation strengthening can be coupled to achieve intelligent deformation and improve ablation resistance through synergistic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Incorporating chitosan (CH)/ammonium polyphosphate (APP) and CH/montmorillonite (MMT) into SiFs, respectively, and found that both CH/APP and CH/MMT could increase the limiting oxygen index (LOI), reduce the peak HRR (PHRR), and smoke production of SiFs [13]. The mechanical properties and flame retardancy of the SiFs composites were significantly improved, and the generation of heat and smoke was inhibited when vinyl-terminated polyborosiloxane filler was mixed into the SiFs matrix [14]. Coating only 0.04 wt% graphene oxide (GO) on the surface of SiFs could significantly reduce its HRR and improve the flame retardancy of SiFs without affecting its density and mechanical flexibility [15].…”
Section: Introductionmentioning
confidence: 99%